2024
DOI: 10.1111/apha.14132
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer‐based sedentary time, light physical activity, and moderate‐to‐vigorous physical activity from childhood with arterial stiffness and carotid IMT progression: A 13‐year longitudinal study of 1339 children

Andrew O. Agbaje,
Alan R. Barker,
Adam J. Lewandowski
et al.

Abstract: AimsWe examined the longitudinal associations of sedentary time (ST), light physical activity (LPA), and moderate‐to‐vigorous PA (MVPA) from childhood with carotid‐femoral pulse wave velocity (cfPWV), a measure of arterial stiffness and carotid intima‐media thickness (cIMT).MethodsWe studied 1339 children, aged 11 years from Avon Longitudinal Study of Parents and Children, UK, followed up for 13 years. Accelerometer‐based ST, LPA, and MVPA were assessed at ages 11, 15, and 24 years clinic visits. cfPWV and cIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…In the present study, it was observed that MVPA from childhood was paradoxically associated with higher fibrosis score, which was mediated (67% mediation) by increased lean mass. This seems a physiologic adaptation of the liver smooth muscle cells to MVPA as previously noted with progressive increased left ventricular mass and vascular wall thickness, but MVPA was not associated with an increased risk of liver cirrhosis 16,32,33 .…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…In the present study, it was observed that MVPA from childhood was paradoxically associated with higher fibrosis score, which was mediated (67% mediation) by increased lean mass. This seems a physiologic adaptation of the liver smooth muscle cells to MVPA as previously noted with progressive increased left ventricular mass and vascular wall thickness, but MVPA was not associated with an increased risk of liver cirrhosis 16,32,33 .…”
Section: Discussionsupporting
confidence: 63%
“…In the latest health guideline, there was no recommendation on LPA due to the scarcity of evidence on device-measured LPA in youth, and it has been established that most youths do not meet the recommended average of 60 minutes of MVPA per day but may accumulate a substantial amount of LPA minutes per day 10 . Several emerging longitudinal studies are reporting that LPA might yield more significant health benefits than MVPA, such as reducing systolic blood pressure, dyslipidaemia, fat mass obesity, insulin resistance, inflammation and vascular stiffness [12][13][14][15][16]30 . Longitudinal studies of accelerometer-based LPA and liver indices in the young population are scarce 3,[8][9][10][11]19,21 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations